2014
DOI: 10.1128/jvi.03833-13
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionarily Conserved Requirement for Core Binding Factor Beta in the Assembly of the Human Immunodeficiency Virus/Simian Immunodeficiency Virus Vif-Cullin 5-RING E3 Ubiquitin Ligase

Abstract: The human immunodeficiency virus type 1 (HIV-1)-encoded virion infectivity factor (Vif) is required to inactivate the host restriction factor APOBEC3 by engaging Cullin 5 (Cul5)-RING ubiquitin ligase (CRL5). Core binding factor beta (CBF-␤) is a novel regulator of Vif-CRL5 function; as yet, its mechanism of regulation remains unclear. In the present study, we demonstrate that CBF-␤ promotion of Vif-CRL5 assembly is independent of its influence on Vif stability and is also a conserved feature of primate lentivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 51 publications
(87 reference statements)
3
23
0
Order By: Relevance
“…Requirement for CBF-b in feline APOBEC3 degradation non-primate lentiviruses have either maintained an ancestral CBF-b-independent mechanism or have evolved to use another co-factor in the same way to degrade APOBEC3 proteins of their ancestral hosts. Interestingly, it has been recently reported that HIV-1 Vif can utilize CBF-b proteins from flies (Drosophila melanogaster) and worms (Saccoglossus kowalevskii) as the co-factor for human APOBEC3 degradation (Han et al, 2014). This further suggests that the usability of CBF-b is not dependent on the hosts and that primate lentiviral Vif has adapted to use CBF-b as an essential cofactor during its evolution.…”
mentioning
confidence: 74%
“…Requirement for CBF-b in feline APOBEC3 degradation non-primate lentiviruses have either maintained an ancestral CBF-b-independent mechanism or have evolved to use another co-factor in the same way to degrade APOBEC3 proteins of their ancestral hosts. Interestingly, it has been recently reported that HIV-1 Vif can utilize CBF-b proteins from flies (Drosophila melanogaster) and worms (Saccoglossus kowalevskii) as the co-factor for human APOBEC3 degradation (Han et al, 2014). This further suggests that the usability of CBF-b is not dependent on the hosts and that primate lentiviral Vif has adapted to use CBF-b as an essential cofactor during its evolution.…”
mentioning
confidence: 74%
“…The N terminus of HIV-1 Vif, particularly the amino acids W5, V7, I9, W11, W21, W38, G84, E88, W89, L106, and I107 (Fig. 6A), was critical for CBF-␤ binding (30,56,(58)(59)(60)(61). These amino acids were almost conserved among primate lentiviral Vifs (Fig.…”
Section: Cbf-␤-kd 293t Cell Generationmentioning
confidence: 97%
“…While intrinsically disordered proteins can generally fold independently of chaperon assistance (44,45), recruitment of these molecular chaperoning factors can facilitate particular interactions. In support of this notion, recent biochemical and structural studies indicated that the disordered viral accessory Vif protein recruits cellular core-binding-factor-␤ (CBF-␤; a transcription cofactor known to form functional complexes with the RUNX family of transcription factors [46]), mainly as a molecular chaperon that increases Vif stability and solubility and induces a specific Vif-conformation mandatory for its interaction with cullin-5 and consequent Vif-E3 ligase assembly (47)(48)(49)(50)(51).…”
Section: Molecular Basis Underlying Flexible Exploitation Of Cellularmentioning
confidence: 94%